Organizational Conflict Transformation: Principal Strategies in Accelerating Educator Performance: (Transformasi Konflik Organisasional: Strategi Kepala Sekolah dalam Mengakselerasi Kinerja Pendidik) - Hidayat, Wahyu; Kaniati, Rosna Dewi (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
The conflict management approach taken by MI Ibrahim Ulum Azmi has an important role in determining the position of the organization as an institution that builds a shared spirit. In the context of the MI Ibrahim Ulum Azmi educational institution, the peak of the conflict became the starting point for making institutional changes and reforms that would encourage the creation of a competitive work climate and collaborative intergroup cooperation. The aims of this study are: (1) Conflict management strategies to improve teacher performance at MI Ibrahim Ulum Azmi. (2) Factors supporting and inhibiting conflict management in improving teacher performance at MI Ibrahim Ulum Azmi. (3) The results of conflict management in improving teacher performance at MI Ibrahim Ulum Azmi. In collecting data, writing uses the interview method. From this research, it can be concluded that conflict management strategies in improving the performance of MI Ibrahim Ulul Azmi teachers first emphasize the importance of open and effective communication in overcoming and resolving conflicts between teaching staff, secondly encourage teamwork and build strong relationships between teachers and school staff , third, apply open communication, cooperation, and constructive conflict resolution. Then regarding the supporting and inhibiting factors of conflict management in improving teacher performance at MI Ibrahim Ulul Azmi, there are several supporting factors, one of which is a culture of open and inclusive communication in schools. Then the importance of the principal as a leader who provides clear direction, provides support. In addition to the supporting factors, of course there are several inhibiting factors that can influence conflict management in improving teacher performance. One is the lack of adequate communication and conflict management skills among teachers. In addition, another factor is the lack of time and sufficient resources to involve all parties involved in the conflict resolution process.